Syngas production from methane reforming processes over boron promoted Ni/SBA-15 catalysts - Singh, Sharanjit (2019)
Non-renewable fossil fuels are currently being exploited at an unprecedented rate to meet the global energy demand. In addition, the increasing depletion of crude oil resources and growing anthropogenic greenhouse gases (i.e., CH4 and CO2) emissions have spurred an initiative to find renewable and environmentally friendly energy sources which can substitute the existing non-renewable fossil fuels and simultaneously reduce greenhouse gas emissions. In this regard, methane dry reforming (MDR) has gained substantial interest since it can be used to convert these greenhouse gases to valuable products. However, MDR utilizes the expensive and complex catalysts, making the technology less economic in the real-world applications. Therefore, the development of cost-effective catalysts materials and advanced process engineering is highly desirable to make this technology economical to produce sustainable energy fuels. In this regard, Ni-based catalysts have been thoroughly investigated for MDR and have shown successful conversion results for syngas production. But these catalysts also exhibit the tendency for coke formation which ultimately results in the catalysts deactivation. Literature suggests that the catalyst deactivation by coke formation can be considerably reduced by increasing the supply of oxidants (i.e. H2O and CO2) and incorporation of promoters. Therefore, this thesis investigates the effect of operating parameters for methane dry reforming and bi-reforming of methane reactions. In addition, the kinetic studies were performed for methane dry reforming by using power law and six different Langmuir-Hinshelwood kinetic rate expressions over 10%Ni/SBA-15 catalyst. Besides, the influence of boron loading (1%, 2%, 3% and 5%) and different promoter (B, Ce, La and Y) was investigated for MDR reaction. The SBA-15 support, unpromoted and promoted catalysts were synthesized by using hydrothermal, incipient-wetness impregnation and sequential impregnation techniques, respectively. The results found a relation between the catalyst activity, feed of each reactant and formation of carbonaceous species for MDR reaction over SBA-15 supported nickel. In fact, the catalysts found both amorphous and graphitic kind of carbonaceous species on the spent catalyst. Initially, activation energy of 91 kJ mol-1 for methane consumption rate was calculated by using the Power-law expression. Furthermore, a single-site dissociative Langmuir-Hinshelwood kinetic mechanism was proposed, with associated activation energy of about 72 kJ mol-1. The catalyst showed high resistance to graphitic carbon formation in the presence of H2O and CO2 oxidizing agents in bi-reforming reaction, whilst re-oxidation of nickel metallic species was observed in the reaction. The results obtained for different boron loading suggested that the 2% of boron was sufficient to achieve high activity and resistance from carbonaceous species. Therefore, the 2%B-promoted catalyst was further compared with other promoted catalysts (La, Ce and Y) under methane dry reforming conditions for 72 h stability test. The results revealed that the yttrium promoted catalyst significantly enhanced the catalytic activity, whereas the boron promoted catalyst exhibited the highest coke resistance among the counterparts.